Thermotolerance of an inactivated rabies vaccine for dogs. Issue 46 (4th November 2016) - Lankester, Felix J.; Wouters, Pieter A.W.M.; Czupryna, Anna; Palmer, Guy H.; Mzimbiri, Imam; Cleaveland, Sarah; Francis, Mike J.; Sutton, David J.; Sonnemans, Denny G.P.
Highlights: Assessment of dogs inoculated with Nobivac Rabies vaccine stored at high temperatures. Neutralizing antibody response not inferior after vaccine stored at 30 °C for 3 months. Nobivac Rabies vaccine likely to be efficacious if exposed to elevated temperatures. Flexible vaccine delivery models can be explored using the Nobivac Rabies vaccine. Abstract: This study provides the first robust data that the antibody response of dogs vaccinated with Nobivac® Rabies vaccine stored for several months at high temperatures (up to 30 °C) is not inferior to that of dogs vaccinated with vaccine stored under recommended cold-chain conditions (2–8 °C). A controlled and randomized non-inferiority study was carried out comparing the four-week post vaccination serological responses of Tanzanian village dogs inoculated with vaccine which had been stored at elevated temperatures for different periods of time with those of dogs vaccinated with the same product stored according to label recommendations. Specifically, the neutralizing antibody response following the use of vaccine which had been stored for up to six months at 25 °C or for three months at 30 °C was not inferior to that following the use of cold-chain stored vaccine. These findings provide reassurance that the vaccine is likely to remain efficacious even if exposed to elevated temperatures for limited periods of time and, under these circumstances, it can safely be used and not necessarily destroyed or discarded. The availability of thermotolerant vaccines has been an important factor in the success of several disease control and elimination programs and could greatly increase the capacity of rabies vaccination campaigns to access hard to reach communities in Africa and Asia. We have not confirmed a 3-year duration of immunity for the high temperature stored vaccine, however because annual re-vaccination is usually practiced for dogs presented for vaccination during campaigns in Africa and Asia this should not be a cause for concern. These findings will provide confidence that, for rabies control and elimination programs using this vaccine in low-income settings, more flexible delivery models could be explored, including those that involve limited periods of transportation and storage at temperatures higher than that currently recommended.